2015
DOI: 10.1016/j.celrep.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Cell Division Timing Accounts for a Shift in the Thermal Limits of C. elegans and C. briggsae

Abstract: Cold-blooded animals, which cannot directly control their body temperatures, have adapted to function within specific temperature ranges that vary between species. However, little is known about what sets the limits of the viable temperature range. Here we show that the speed of the first cell division in C. elegans N2 varies with temperature according to the Arrhenius equation. However, it does so only within certain limits. Outside these limits we observe alterations in the cell cycle. Interestingly, these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 39 publications
11
89
0
Order By: Relevance
“…Manual lineaging was performed at 23°C. To compare cell cycle times between manual lineaging and automated imaging, manually obtained values were scaled to presumptive 20°C values via an Arrhenius law extracted from the molting data at different temperatures in (Hirsh et al, 1976) (scaling factor 1.24, (see also (Begasse et al, 2015)).…”
Section: Methodsmentioning
confidence: 99%
“…Manual lineaging was performed at 23°C. To compare cell cycle times between manual lineaging and automated imaging, manually obtained values were scaled to presumptive 20°C values via an Arrhenius law extracted from the molting data at different temperatures in (Hirsh et al, 1976) (scaling factor 1.24, (see also (Begasse et al, 2015)).…”
Section: Methodsmentioning
confidence: 99%
“…Above 258C, the rate of defective cell divisions rapidly increases with increasing temperature and adult animals become progressively sterile. Asymmetry during cell divisions-which is highly precise between 12 and 258C-becomes tenuous; with 19.4% embryos failing to divide asymmetrically (Begasse et al, 2015). These findings indicate that certain aspects of polarity maintenance and hence the first asymmetric cell division are heat-labile ( Fig.…”
Section: Introductionmentioning
confidence: 90%
“…In poikilotherms, the body temperature is not subject to thermal homeostasis, thus, these organisms have to search for ambient temperatures that match their physiological requirements. It has been recently shown that the optimal ambient temperature range for the nematode C. elegans is 8 2 258C (Begasse et al, 2015;Neves et al, 2015). Above 258C, the rate of defective cell divisions rapidly increases with increasing temperature and adult animals become progressively sterile.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of vitelline membrane as a mechanical confinement on embryonic cell division has never been investigated. Previous works have shown the effects of temperature on mechanical properties of fiber-rich biological gels (Tempel, Isenberg & Sackmann, 1996;Xu, Wirtz & Pollard, 1998;Semmrich et al, 2007), suspended (Chan et al, 2014) and embryonic cells (Marsland & Landau, 1954;Mitchison & Swann, 1954) as well as timing of cell division (Begasse et al, 2015). However, the effects of temperature on division of vitelline-confined embryonic cells have not been investigated.…”
Section: Introductionmentioning
confidence: 99%